2018
DOI: 10.1247/csf.18026
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid GM2 Induces Invasiveness in Irradiation-tolerant Lung Cancer Cells

Abstract: Glycans, including glycosphingolipids, are broadly expressed in plasma membranes and play important roles in cell-cell interactions. Recently, it has been revealed that glycans participate in the regulation of malignant phenotypes of cancer cells, e.g. growth and invasion. However, their roles in irradiation-tolerant cancer cells have not yet been elucidated. In this study, we show that specific glycosphingolipids are highly expressed in invasive, irradiation-tolerant lung cancer cells. Particularly, the glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…At the cellular level, we showed that B3GNT5 and GAL3ST1 differentially regulated cancer cell proliferation, migration, invasion, sphere formation as well as in vivo tumor growth. Consistent with this finding, the intracellular level of lacto/neolacto-series glycosphingolipid and sulfatide has been recently implicated in controlling cancer cell properties [40,48]. Interestingly, sphingolipidomics analysis of B3GNT5/GAL3ST1 genetically perturbed lung cancer cell lines confirmed their regulatory role in sphingolipid metabolism, indicating that their expression differentially regulated the synthesis of lacto/neolacto-series glycosphingolipid and sulfatide in order to determine sphingolipid metabolic reprogramming in lung cancer cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…At the cellular level, we showed that B3GNT5 and GAL3ST1 differentially regulated cancer cell proliferation, migration, invasion, sphere formation as well as in vivo tumor growth. Consistent with this finding, the intracellular level of lacto/neolacto-series glycosphingolipid and sulfatide has been recently implicated in controlling cancer cell properties [40,48]. Interestingly, sphingolipidomics analysis of B3GNT5/GAL3ST1 genetically perturbed lung cancer cell lines confirmed their regulatory role in sphingolipid metabolism, indicating that their expression differentially regulated the synthesis of lacto/neolacto-series glycosphingolipid and sulfatide in order to determine sphingolipid metabolic reprogramming in lung cancer cells.…”
Section: Discussionmentioning
confidence: 53%
“…After culturing for 24 h, 10 ml CCK-8 reagent was added to each well. Similarly, 100 ml complete medium containing 10 ml CCK-8 solution was added to respective wells at different time points (12,24,36,48 and 60 h). The plates were incubated in dark at 37°C for 2 h, and absorbance at 450 nm wavelength was measured.…”
Section: Cell Proliferation Colony Formation Migration Invasion Assays and Sphere Formation Assaymentioning
confidence: 99%
“…GM2 gangliosides are glycans. Several functions of glycans have been implicated in cancers (72,73), and GM2 promotes tumor cell invasion and migration (74)(75)(76). GM2 accumulates in lysosomes as a functional consequence of specific mutations in GM2A or its partners in GM2 degradation, HEXA and HEXB (77,78).…”
Section: Jiang Et Almentioning
confidence: 99%
“…It has been long known that GM2, which is rather weakly expressed in normal tissue, is highly abundant in several human malignant tumors, including melanomas, gliomas, and neuroblastomas [ 91 ]. Recent studies confirm that GM2 induces invasiveness in irradiation‐tolerant human lung adenocarcinoma cells [ 92 ] and promotes invasion and hence malignancy of human pancreatic ductal adenocarcinoma cells [ 93 ]. In contrast to ganglioside GM2, its direct descendent GM1 was shown to exert anticancerous effects.…”
Section: Step 2: Invasionmentioning
confidence: 99%